Angiosarcoma after adjuvant radiotherapy in high-risk squamous cell carcinoma of the vulva: a case report - Laliscia, Concetta; Gadducci, Angiolo; Pollina, Luca; Paiar, Fabiola (Menopause Review/Przegląd Menopauzalny, 2019)
Squamous cell carcinoma of the vulva represents 3-5% of gynecological cancers. The incidence is higher in postmenopausal patients; the mean age of women with vulvar cancer is between 64 and 70 years. Radiotherapy plays an increasing role in the treatment of high-risk squamous cell carcinoma of the vulva; associated with surgery it significantly improves prognosis but is also associated with serious late side-effects, such as secondary malignancies. We describe a case of a 75-year-old woman who underwent deep total vulvectomy with inguinal-femoral lymphadenectomy for high-risk, keratinizing variant HPV-negative, squamous cell carcinoma of the vulva, followed by adjuvant concomitant chemo-radiotherapy, at the University Hospital of Pisa in February 2013. Five years later she developed a very large angiosarcoma in the right abdominal wall, at the edge of the previous radiotherapy field, and underwent radical surgery. After four months, she developed bone metastasis of angiosarcoma, also treated with surgery. This experience shows that the use of new technologies allows the delivery of high doses of radiotherapy, significantly correlated with a better prognosis, but also associated with fortunately rare morbidity, such as radiation-induced angiosarcoma. Due to the presence of long, mostly post-menopausal survivors among irradiated patients, screening for second malignancies must be developed for selected high-risk survivor groups.